Writers and revolution : intellectuals and the French Revolution of 1848 - Beecher, Jonathan (Cambridge : Cambridge University Press, 2021)
The revolution of 1848 has been described as the revolution of the intellectuals. In France, the revolution galvanised the energies of major romantic writers and intellectuals. This book follows nine writers through the revolution of 1848 and its aftermath: Alphonse de Lamartine, George Sand, Marie d'Agoult, Victor Hugo, Alexis de Tocqueville, Pierre-Joseph Proudhon, Alexander Herzen, Karl Marx, and Gustave Flaubert. Conveying a sense of the experience of 1848 as these writers lived it, this fresh and engaging study captures the sense of possibility at a time when it was not yet clear that the Second French Republic had no future. By looking closely at key texts in which each writer attempted to understand, judge, criticise, or intervene in the revolution, Jonathan Beecher shows how each endeavoured to answer the question posed explicitly by Tocqueville: Why, within the space of two generations, did democratic revolutions twice culminate in the dictatorship of a Napoleon?
Prologue -- Lamartine, the Girondins and 1848 -- George Sand: "The People" found and lost -- Marie d'Agoult, a liberal republican -- Victor Hugo: the Republic as a learning experience -- Tocqueville: "a vile tragedy performed by provincial actors" -- Proudhon: "a revolution without an idea" -- Alexander Herzen: a tragedy both collective and personal -- Marx: the meaning of a farce -- Flaubert: lost hopes and empty words -- Aftermath, themes and conclusion.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: French literature -- 19th century -- History and criticism; France -- History -- February Revolution, 1848 -- Literature and the revolution; France -- History -- 1848-1870.; France -- History -- February Revolution, 1848 -- Influence